2019
DOI: 10.3892/etm.2019.7177
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of circulating microRNAs in heart failure (Review)

Abstract: Heart failure (HF) is a complex clinical syndrome, characterized by inadequate blood perfusion of tissues and organs caused by decreased heart ejection capacity resulting from structural or functional cardiac disorders. HF is the most severe heart condition and it severely compromises human health; thus, its early diagnosis and effective management are crucial. However, given the lack of satisfactory sensitivity and specificity of the currently available biomarkers, the majority of patients with HF are not dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 123 publications
(73 reference statements)
0
28
0
2
Order By: Relevance
“…For example, during myocardial ischemia, the level of miR-21 decreases sharply, and supplementing its expression reduces the size of the attack and delays the development of HF [51]. It was also proposed that miR-21 could be an indicator of late age in ischemic heart failure [52]. Numerous studies indicate that both the heart and circulatory miR-21 correlate with the degree of cardiac fibrosis [53].…”
Section: Resultsmentioning
confidence: 99%
“…For example, during myocardial ischemia, the level of miR-21 decreases sharply, and supplementing its expression reduces the size of the attack and delays the development of HF [51]. It was also proposed that miR-21 could be an indicator of late age in ischemic heart failure [52]. Numerous studies indicate that both the heart and circulatory miR-21 correlate with the degree of cardiac fibrosis [53].…”
Section: Resultsmentioning
confidence: 99%
“…Our bioinformatics analysis found ACE2 was significantly down-regulated in SARS-CoV-2 infected CMs, which was consistent with the prior reports of examining SARS-CoV-2 infected myocardium [ 50 ]. SARS-CoV-2 mediated myocardial apoptosis, cardiogenic shock, myocardial ischemia and inflammatory injury were related to the down-regulation of ACE2 in the myocardium [ [51] , [52] ]. The spike protein of SARS-CoV-2 might bind to TLR4 to trigger transmembrane stimulation [ [53] , [54] ].…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al reported a novel function of miR-147b in protecting barrier function in human vascular endothelial cells, which affects CVDs, and expression of microR-147 in CAD patients was reported less compared to the controls [ 113 ]. Yao-Meng et al [ 109 ] reported lower expression miR-147 in patients with dilated cardiomyopathy (DCM) compared with control subjects, suggesting its role as a potential diagnostic biomarker [ 114 ]. Mingxia Gu et al have shown that miR-147b inhibits viability and promotes cell apoptosis, which has a role in the pathogenesis of heart failure [ 115 ].…”
Section: Role Of Micror-147b In Cadmentioning
confidence: 99%